An equity perspective on access to, enrolment in and finance of tertiary education - Rita Asplund; Oussama Ben-Abdelkarim; Ali Skalli (The Research Institute of the Finnish Economy (ETLA), 2007)
The failure to achieve equitable access to university studies has turned the focus to the funding of European higher education systems. Since the large amounts of public subsidies injected in tertiary-level education have not succeeded in reducing disparities in access for children from different social backgrounds, this is seen as compelling evidence for there being a need to revise higher education financing not only on efficiency but also on equity grounds. Such policies are already pursued, planned or intensively discussed in most of Europe. More equitable access to and participation in university education through changes in the funding sources and mechanisms is a challenging policy with long-term implications. Hence, it should preferably be based on reliable empirical evidence. This raises the question of what the theoretical and empirical literature actually tells us about these matters. How severe is the under-representation of students from a socially disadvantaged background? Has this inequality changed over time across and within European countries? What role does funding play? Have the changes in funding systems already undertaken in several European countries improved the participation of students from low-income families? This review paper aims to answer these important questions by drawing together the available evidence, by contrasting it against pursued educational policies and by pointing to still existing knowledge gaps.
Keywords: I22; 330; access; equity; financing; tertiary education; Studienfinanzierung; Bildungspolitik; Studierende; Bildungschancen; EU-Staaten